Stress dependent impedance spectroscopy of niobium based ceramics - Tanaka, Hideki; Nozaki, Takumi; Martin, Alexander; Webber, Kyle Grant; Kakimoto, Ken Ichi (Japanese Journal of Applied Physics, 2023)
In this study, stress-dependent impedance spectra were characterized as a function of uniaxial compressive stress up to -300 MPa for Zr-doped (Na0.5K0.5)(Nb1−x/125Zrx/100)O3−δ (x = 5, 10 mol%). This allowed for the evaluation of the stress-induced changes in the grain and grain boundary capacitance. The grain capacitance from equivalent circuit fitting exhibited decreasing behavior with increasing uniaxial compressive stress increased, which is attributed to hindered domain wall movement reducing the extrinsic contributions. Interestingly, NKNZ10 showed a more significant degradation in grain capacitance than NKNZ5. One possible explanation is the difference in oxygen vacancies, and by extension defect dipoles, when introducing Zr into the lattice. As such, this study reveals the amplifying effect of oxygen vacancies to the mechanical suppression of domain wall movement.
CRIS-Team Scopus Importer:2023-09-15
Keywords: defect dipole; ferroelasticity; lead free ferroelectrics; stress dependent impedance spectroscopy